Produção de biofilme em isolados de Candida spp do Hospital das Clínicas de Botucatu, UNESP - Nascimento, Ariane Cristina Mendes de Oliveira Bruder [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Over the last decade, there have been important changes in the epidemiology of Candida infections and antifungal agents used to treat these infections. In recent years, Candida species have emerged as important causes of invasive infections mainly among immunocompromised patients. The principal aim of this study was to evaluate the epidemiology of infectious Candida species isolated in our hospital and accordingly supply data for hospital infection control The other aims were to compare the traditional, automated and molecular methods used to identify Candida isolates to the species level current available in the Clinical Hospital of the Boucatu Medical School, UNESP, to evaluate the drug susceptibility as well as to biofilm production by this yeasts and to characterize, by molecular tools, several genes involved in biofilm production of C. albicans and C. parapsilosis and the use of group I introns to genotype the species C. albicans. A total of 196 Candida strains that were isolated from blood specimens of hospitalized patients were included in the study. The most common Candida species identified were C. albicans (39,3-44,4%) and C. parapsilosis (33,2-42,3%). According to the insertion of group I introns, the genotype A of C. albicans were the most frequent (74%). The evaluation of traditional phenotypic methods, the automated and some molecular revealed good agreement (>80%) and since both phenotypic methods were simple and cost effective and automated were few time-consuming when compared to molecular techniques, they should be considered in the routine lab identification of Candida species. The chromogenic media must be employed to avoid misinterpretations, independently of the method used. Antifungal susceptibility testing was performed by the reference microdilution method (CLSI) and all strains showed good susceptible against the drugs evaluated (fluconazole, voriconazole, anidulafungin and ...

Nas últimas décadas, a epidemiologia das infecções por Candida spp. e o perfil de susceptibilidade a drogas vêm sofrendo importantes alterações. A emergência dessas espécies, como agente de infecções invasivas, tem se destacado principalmente entre pacientes imunocomprometidos. O principal objetivo desse estudo foi avaliar a epidemiologia das infecções por Candida spp. no Hospital das Clínicas da Faculdade de Medicina de Botucatu, UNESP, e auxiliar no suprimento de dados para o melhor controle da infecção hospitalar. Os objetivos específicos incluíram a comparação entre as metodologias tradicional, automatizada e molecular de identificação em nível de espécie atualmente disponíveis nesta instituição, avaliar o perfil de susceptibilidade aos antifúngicos, bem como a produção de biofilme por estes isolados e caracterizar, utilizando ferramentas de biologia molecular, genes envolvidos na produção de biofilme de C. albicans e C. parapsilosis e o emprego dos introns do grupo I para genotipagem de C. albicans. Um total de 196 isolados de Candida spp. provenientes de hemocultura de pacientes foram avaliados. As espécies mais frequentes foram C. albicans (39,3 44,4%) e C. parapsilosis (33,2-42,3%). Foi observada boa correlação (>80%) entre os métodos de identificação avaliados – fenotípico tradicional, automatizado e molecular; e a caracterização dos introns do grupo I detectou predominância de C. albicans genótipo A (74%). O método tradicional é o mais simples e de baixo- custo, e o método automatizado mais rápido na liberação do resultado, quando comparados às técnicas moleculares, as quais apresentam maior poder discriminatório. Sugere-se a utilização do meio cromogênico, em paralelo ao método de identificação selecionado, para auxiliar na interpretação dos resultados, principalmente nas espécies mais frequentes. O método empregado em laboratórios de rotina deve ser considerado quando ...
Keywords: Candida albicans; Biofilme; Antimicóticos; Infeccão hospitalar